Answer:
$
Step-by-step explanation:
Answer:

Step-by-step explanation:
The given Equation is
.................(i)
Adding (
) on both sides of (i)
solving and cancelling out the terms will give
⇒
⇒
...................(ii)
Now we Know that
Applying this on equation (ii)

This will lead us to
Either 2x-3 =0 .......(iii) or 2x+3=0 ..........(iv)
Solving equation (iii) for value of x
2x - 3 =0
adding 3 on both sides
2x -3 +3 = 0+ 3
2x = 3
Cross multiplying gives

Solving equation (iv) for value of x
2x + 3 =0
adding -3 on both sides
2x -3 +3 = 0- 3
2x = -3
Cross multiplying gives

so
and 
Step 1: Multiply the Principal, which is the amount borrowed, by the interest rate.
Step 2: Compute compound interest using the following formula: A= P(1+r/n)
Hope this helps u
Answer:
Step-by-step explanation:
(x^4 + 2x^3 - 7x - 9) +
(x^5 - 2x^4 + 8x + 18)
x^5 - x^4 + 2x^3 + x + 9
Answer:
165°
Step-by-step explanation: